Density and surface tension of molten cast irons - Fima, Przemyslaw; Sobczak, Natalia (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Computer-aided development of liquid-assisted metallurgical processes requires reliable basic data for the molten materials, including thermophysical properties such as density, surface tension and viscosity. Cast irons belong to the group of Fe-C alloys of practical importance due to their good technological and utility properties, yet experimental thermophysical data of cast irons in the literature are scarce. In this study, the density and surface tension of three compacted graphite cast iron alloys were measured by the sessile drop method in contact heating mode in the temperature range of 1473 – 1723 K with polycrystalline alumina as a substrate. The drop profile images were recorded both during heating and subsequent cooling regimes. At 1473 K, the density values of the studied compacted graphite irons are between 6.66 and 6.69 g*cm-3 , whereas surface tension values are between 1130 and 1510 mN*m-1. The density decreases with increasing temperature, while surface tension dependence on temperature is less obvious. The obtained results are compared to the available literature data and analyzed taking into account chemical interaction of liquid cast irons with the substrate material.